Investigating the Degrowth Paradigm through prospective Modeling - Briens, François; Maïzi, Nadia (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
Dynamic models of the economy that adequately incorporate different values and high levels of uncertainty can give insights into the effects of degrowth proposals. Participative processes should be used to avoid questionable assumptions about human behavior like the homo oeconomicus.